2021
DOI: 10.3389/fimmu.2021.624746
|View full text |Cite
|
Sign up to set email alerts
|

The Macrophage Response Is Driven by Mesenchymal Stem Cell-Mediated Metabolic Reprogramming

Abstract: Mesenchymal stem cells (MSCs) are multipotent adult stromal cells widely studied for their regenerative and immunomodulatory properties. They are capable of modulating macrophage plasticity depending on various microenvironmental signals. Current studies have shown that metabolic changes can also affect macrophage fate and function. Indeed, changes in the environment prompt phenotype change. Therefore, in this review, we will discuss how MSCs orchestrate macrophage’s metabolic plasticity and the impact on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 195 publications
(330 reference statements)
0
16
0
Order By: Relevance
“…It can thus be hypothesized that macrophages respond to the necrotic disrupted bone marrow mesenchymal cells. The crosstalk between mesenchymal cells and macrophages in the development of disease and maintenance of homeostasis of inflammatory microenvironments became a research focus [ 18 , 19 ]. However, evidence supporting a role of damaged mesenchymal cell to modulate osteoclastogenesis and macrophage polarization [ 20 ] is limited.…”
Section: Introductionmentioning
confidence: 99%
“…It can thus be hypothesized that macrophages respond to the necrotic disrupted bone marrow mesenchymal cells. The crosstalk between mesenchymal cells and macrophages in the development of disease and maintenance of homeostasis of inflammatory microenvironments became a research focus [ 18 , 19 ]. However, evidence supporting a role of damaged mesenchymal cell to modulate osteoclastogenesis and macrophage polarization [ 20 ] is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-10, also associated with the expression of ASPS, IGF1 and its receptor IRS-1, clearly has chondroprotection activity, stimulating the expression of collagen type II and proteoglycan and regulating the maintenance of tissue integrity [ 48 ]. Moreover, our results demonstrated that adipose tissue also hosts chemokines such as 11β-HSD1, PPARγ, and adiponectin which have been shown to contribute to immunoregulation through modulation of hMSC metabolism [ 49 , 50 ], but also chemokines such as MCP1, Visfatin, and Resistin which have been shown to contribute to immunoregulation through modulation of macrophages plasticity [ 51 ]. Beyond that, adiponectin, ASPS, MCP1, Visfatin, and Resistin, when taken together, prove that they can contribute to the diagnosis of OA, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory macrophage polarization is characterized by enhanced glycolysis and pentose phosphate pathways and decreased oxidative phosphorylation. In contrast, anti-inflammatory macrophage polarization is characterized by enhanced oxidative phosphorylation, and anti-inflammatory macrophages rely on oxidative phosphorylation for energy production ( 118 121 ). MSCs can induce anti-inflammatory macrophage polarization and promote tissue repair through metabolic reprogramming ( 122 ).…”
Section: How Mscs Regulate Macrophage Polarizationmentioning
confidence: 99%